Renal sympathetic denervation for resistant hypertension: where do we stand after more than a decade - Fontes,Marco Antônio Peliky (2020)
Abstract Despite the current availability of safe and efficient drugs for treating hypertension, a substantial number of patients are drug-resistant hypertensives. Aiming this condition, a relatively new approach named catheter-based renal denervation was developed. We have now a clinically relevant time window to review the efficacy of renal denervation for treating this form of hypertension. This short review addresses the physiological contribution of renal sympathetic nerves for blood pressure control and discusses the pros and cons of renal denervation procedure for the treatment of resistant hypertension.